Potensi dan Strategi Pengembangan Produksi Porang di Kabupaten Madiun - Naomy Intan Della; Astuti Andjar; Ratna Mega Sari; Suherman Suherman; Sri Mulyati (JURNAL AGRIBISNIS TERPADU, 2023)
Madiun Regency is the central of porang producing in Indonesia. Porang cultivations have been done because porang is Madiun’s main export commodity. However, the amount of porang produced every year has not meet the international market demands. Therefore, this research was aimed to analyze the potential for cultivation development and to determine the strategy to be used for the porang production’s development. The research was occurred at Klangon and Lembah village and the methods that were done in this research were Index Potential Analysis, IFE and EFE Matrix, SWOT Analysis, and SWOT Matrix. The analyzed result showed the production unit was really good in supporting the porang’s cultivation in Madiun Regency. SWOT analysis came to show that the proper strategy to be used in developing porang cultivation is by keeping the quality, adding equipment and others supporting utilities, enhancing coorporation with purchasing companies, increasing the coorporation amongst the farmers, and doing extensification cultivations of optimizing the existing resources.Keyword: Porang Production, Export Commodity, Index Potential, Development Strategy